Artificial night lighting disrupts sex pheromone in a noctuid moth - VAN GEFFEN, KOERT G.; GROOT, ASTRID T.; VAN GRUNSVEN, ROY H. A.; DONNERS, MAURICE; BERENDSE, FRANK; VEENENDAAL, ELMAR M. (Ecological entomology, 2015)
1. One major, yet poorly studied, change in the environment is the increase in nocturnal light pollution. Although this strongly alters the habitat of nocturnal species, the ecological consequences are poorly known. Moths are well known to be attracted to artificial light sources, but artificial light may affect them in other ways as well. 2. In this study, female Mamestra brassicae moths were subjected to various types of low‐intensity artificial night lighting with contrasting spectral compositions (green‐rich, red‐rich, warm white) or to a dark control treatment and the effects on their sex pheromone production and composition were tested. 3. Artificial night lighting reduced sex pheromone production and altered the chemical composition of the pheromone blend, irrespective of spectral composition. Specifically, amounts of the main pheromone component Z11 ‐16: Ac were reduced, while the deterring compounds Z9 ‐14: Ac , Z9 ‐16: Ac , and Z11 ‐16: OH were increased relative to Z11 ‐16: Ac when females were kept under artificial light. These changes may reduce the effectiveness of the sex pheromones, becoming less attractive for males. 4. These results show for the first time that artificial light at night affects processes that are involved in moth reproduction. The potential for mitigation through manipulation of the spectral composition of artificial light appears limited.